Internalisasi nilai moderasi beragama pada anak usia dini Melalui pembiasaan dan keteladanan - Asrowi, Asrowi (LPPM STAI La Tansa Mashiro, 2025)
This study examines the internalization of religious moderation values in early childhood through habituation and teacher role-modeling at RA Al-Inshof, Kaduagung Timur, Cibadak, Lebak, Banten. Employing a phenomenological mixed-methods approach involving observation, in-depth interviews, documentation, and supportive quantitative data, the research explores how teachers, school leaders, parents, and young learners engage in practices that shape moderate attitudes. The findings reveal that daily routines such as greeting, collective prayer, queuing, sharing, and peaceful conflict resolution significantly strengthen children’s tolerance, empathy, and cooperative behavior. Teacher role-modeling through polite communication and inclusive actions emerges as the most influential factor, indicated by a 0.35 score difference between children who receive consistent modeling and those who do not. Overall, the level of moderate behavior among children is categorized as high (mean = 3.38). The study concludes that consistent habituation and authentic teacher role-modeling serve as effective strategies for fostering moderate character from an early age.. Keywords: Moderation, Early Childhood, Role-Modeling.